Antisipasi Monopoli dan Persaingan Usaha Tidak Sehat di Bidang Telekomunikasi Melalui Perda Kabupaten Kampar No.2 Tahun 2009 Tentang Pembangunan dan Penggunaan Menara Bersama Telekomunikasi - Yuli Heriyanti; Ahmad Zikri (Universitas Pahlawan Tuanku Tambusai, 2020)
The birth of Law No. 9 of 2015 concerning Amendments to Law N0. 23 of 2014 concerning Local Government, creates regional authority and power in terms of regional financial management and implementation of development in the regions. The implementation of development in the regions does not have to always rely on funds from the regional expenditure budget, but must also strive for funds or sources that come from the community. Therefore, to support the existence of community participation in advancing the region both morally and materially, the Kampar District Government made Perda No. 2 of 2009 concerning the Construction and Use of Joint Telecommunication Towers. The existence of this Perda is basically protecting the community and the environment and regulating the availability of land / land for the construction of the joint telecommunications tower. In accordance with the times and the level of population growth, especially in Kampar Regency, indirectly also affects the availability of land / land to carry out the tower construction. The construction of this joint telecommunication tower also affects regional income and income for the community